Additions to the genus Demonax Thomson, 1860 (Coleoptera: Cerambycidae: Cerambycinae) from Vietnam - Quynh Nga, Cao Thi; Long, Khuat Dang; Thinh, Ta Huy (Academia Journal of Biology, 2016)
This paper presented a checklist of twenty eight species of the genus Demonax Chevrolat from Vietnam, of those thirteen species are newly recorded for the Vietnam’s fauna, viz. Demonax alcanor Gressitt & Rondon, 1970; Demonax gracilestriatus Gressitt & Rondon, 1970; Demonax izumii Mitono, 1942;  Demonax kheoi Gressitt & Rondon, 1970; Demonax literatus literatus Gahan, 1894; Demonax literatus nansenensis Pic, 1903; Demonax mali Gressitt, 1951; Demonax mulio Pascoe, 1869; Demonax nebulosus Gressitt & Rondon, 1970; Demonax ordinatus Pascoe, 1869; Demonax pseudonotabilis Gressitt & Rondon, 1970;  Demonax occultus Gressitt & Rondon, 1970;  Demonax pseudotristiculus Gressitt & Rondon, 1970. Regarding the distribution of species, twenty eight species are restrictively recorded in the oriental region, and other three species are recorded from Vietnam only. Of the total already known twenty eight Demonax species from Vietnam, three species that were originally described from specimens collected from Vietnam, are currently known only from their type localities, seven species are widely distributed in the country, sixteen species are recorded in northern Vietnam and five species are known from central region and southern Vietnam.